PENERAPAN UNDANG-UNDANG NOMOR 39 TAHUN 2014 TENTANG PERKEBUNAN TERHADAP PELAKU PENCURIAN KELAPA SAWIT - Hengki Syahyunan; Khairuddin Hasibuan; Hilaman Arfandy Siregar; Edy Pane; Lelisari Lelisari (Universitas Labuhanbatu, 2022)
There are different points of view that cause unrest in the community related to the certainty of law enforcement of palm oil theft in Indonesia. The weak law enforcement against palm oil theft is due to the issuance of Supreme Court Regulation Number 2 of 2012 concerning the Adjustment of the Limits for Minor Crimes which translates the value of currency in article 364 of the Criminal Code and others which was originally IDR 250 read into IDR 2,500,000. Laws, Theft, Plantations. This has become a polemic in the community because it has implications for the many acts of palm oil theft whose loss value is not more than the provisions mentioned above so that it does not entangle the perpetrators and does not provide a deterrent effect to the perpetrators of palm oil theft. On the other hand, this Supreme Court Regulation can be overridden by Law Number 39 of 2014 concerning Plantations which can ensnare perpetrators of oil palm theft if the perpetrators harm the Legal Entity Plantation. It is reviewed in several decisions of the Rantauprapat District Court, that there is a verdict against the perpetrators of palm oil theft whose loss value is not more than Rp 2,500,000, but the verdict is sentenced to 6 months in prison. This consideration refers to article 107 letter d of Law Number 39 of 2014 concerning Plantations.Keywords: Law Application, Theft, Plantation